1982
DOI: 10.1002/aic.690280222
|View full text |Cite
|
Sign up to set email alerts
|

A chemical theory for the thermodynamics of highly‐solvated liquid metal mixtures

Abstract: SCOPEThe proper use of liquid metals as solvents makes possible a wide range of new and advantageous chemical processes. For example the carbothermic reduction of reactive metal oxide ores in appropriate solvents could represent very substantial savings over the conventional, highly energy-intensive electrochemical production of aluminum, magnesium, and titantium. Traditionally the refining of pure reactor grade zirconium from ziconia by chemical separation of the hafnium impurities has been most difficult, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Higher negative heat of formation values of Mg 2 Sn were reported by Sharma [127], Eldridge et al [245] and Biltz and Holverscheit [250] than those by Nayeb-Hashemi and Clark [239]. NayebHashemi and Clark [239] along with others like Egan [254], Eckert et al [255], Pavlova and Poyarkov [256] optimized the phase diagram using measured thermodynamic data. Very recently, Jung and Kim [257], Meng et al [258] and Kang and Pelton [259] optimized the same system and modeled the liquid phase by the MQM.…”
Section: Mg-sn (Magnesium-tin)mentioning
confidence: 99%
“…Higher negative heat of formation values of Mg 2 Sn were reported by Sharma [127], Eldridge et al [245] and Biltz and Holverscheit [250] than those by Nayeb-Hashemi and Clark [239]. NayebHashemi and Clark [239] along with others like Egan [254], Eckert et al [255], Pavlova and Poyarkov [256] optimized the phase diagram using measured thermodynamic data. Very recently, Jung and Kim [257], Meng et al [258] and Kang and Pelton [259] optimized the same system and modeled the liquid phase by the MQM.…”
Section: Mg-sn (Magnesium-tin)mentioning
confidence: 99%
“…The utility of different expressions based on semiempirical interpretations such as the Wohl expansion, the Scatchard formula, the van Laar equation, the Wilson equation, and the NRTL equation are discussed by Tomiska (1980) and Eckert et al (1982) and were shown to be generally not applicable for regression of experimental data. Despite the higher temperatures, the interatomic forces are a great deal stronger for metals, and few mixtures exhibit anything like ideality.…”
Section: Introductionmentioning
confidence: 99%
“…The calculational method is straightforward and has been described recently byEckert et al (1982), as the Liquid-liquid coexistence curve for the aluminum-indium system calculated with the physical theory model.1 o Predel m i Sandip' Equilibrium phase d i a g r d of the aluminum-tin system.…”
mentioning
confidence: 99%
“…More recently it has become apparent that many high-temperature processes can be run in liquid metal solutions quite successfully, if the thermodynamic behavior of the mixture can be modeled. Intermolecular forces in metals are a great deal stronger than those in hydrocarbons; so, in spite of the very high temperatures, solution nonidealitics in liquid metal solutions are significantly greater than those observed in organic solutions, and the common methods for representing solution behavior simply do not work for metals (Eckert et al, 1982a).…”
Section: Introductionmentioning
confidence: 99%
“…This paper describes a method for the representation of physical interactions in metal solutions, excluding mixtures which are strongly solvated by the formation of intermetallic compounds. Methods for describing liquid metal thermodynamics strictly in terms of intermetallic compound formation are described by Eckert et al (1982a) and by Alger and Eckert (1983). Recently, Stoicos and Eckert (1983) have demonstrated that these two types of representations can be profitably combined to characterize certain classes of metal mixtures.…”
Section: Introductionmentioning
confidence: 99%